JOURNAL READING TASK: METHOD FOR MEDICAL STUDENTS TO LEARN HEALTH COMMUNICATION - Violantina Linardi; Rizma Adlia Syakurah (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2022)
Background: COVID-19 became world health problem because of its rapid transmission among humans. Cause of that, Ministry of Education and Culture in Indonesia negated class at school and changed it to online class at home. But for some courses like communication, the students must communicate directly to the interlocutor. An online-based health communication learning model is required so that health communication learning continues to run optimally. This study aims to evaluate the new ways of learning health communication through reading journals and delivered in various media.Case study: The communication courses begin with a journal reading task based on predetermined Topics. This task is done in groups, and consists of 5 to 6 peoples. Then, the journal must be submitted in various educational media such as slide presentations, posters, or videos (participants are free to choose the media used) and will be presented via live Instagram or Zoom. Evaluation of this task was conducted to analyze the skills of communication and was assessed by their seniors in medical profession students of Sriwijaya University (peer review). The students was also give feedback (voluntarily) through the questionnaire on this task. Total of 40 presentations and educational media has been evaluated. Most of the students choose poster as their media promotion. The scoring is closed to balance, 55% enough and 45% good (discussion). Connection failure (60.63%) was the main problem that arise when they present the task.Conclusion: Students skill for making media promotion as they props for present the journal was good. The report and presentation of this task was satisfying. The students feel to have the effect of increasing their ability and personal knowledge on health communication. This task was effective for medical students to learn about health communication.